Inclusive and Ecologically-Sound Food Crop Cultivation at Tropical Non-Tidal Wetlands in Indonesia - Benyamin Lakitan; Lindi Lindiana; Laily I. Widuri; Kartika Kartika; Erna Siaga; Mei Meihana; Andi Wijaya (AGRIVITA, Journal of Agricultural Science, 2019)
Productivity and cropping intensity on non-tidal wetland in South Sumatra are considerably low and has been underutilized up to now. The majority of farmers in this ecosystem are smallholders with limited adoption capacity on introduced technologies and modern agricultural practices. The objectives of this research were (1) to comprehensively capture multidimensional constrains that restrained local farmers in increasing their agricultural productivity; and (2) to identify, assess, and develop substantially-relevant, financially-affordable, and socially-acceptable agricultural technologies and practices for smallholder farmers to increase productivity. This research was organized in three main activities: qualitative research employing Grounded Theory procedure, quantitative questionnaire-guided survey, and a series of laboratory and field experiments. The research results indicated that the main constraints in increasing productivity and cropping intensity on the non-tidal wetland in South Sumatra include (1) unpredictable flooding occurrence and low soil nutrients content (agronomic constraint), (2) low financial and technology adoption capacity of local farmers (economic constraint), and (3) public policy has not significantly escalated farmer’s motivation to increase food production (social and institutional constraint). This research suggests that multidimensional (technical, financial, ecological, and socio-cultural) approaches should be integrated in collective efforts for sustainably intensifying food production on the non-tidal wetland.